SERUM SOLUBLE FMS-LIKE TYROSINE KINASE-1 (SFLT-1) LEVEL AT THIRD TRIMESTER OF PREGNANCY AND ONE MONTH FOLLOWING DELIVERY IN WOMEN WITH PREECLAMPSIA (Iraqi Journal of Medical Sciences, 2016)
Background: Preeclampsia is characterized by abnormal vascular response to placentation that is associated with increased systemic vascular resistance, enhanced platelet aggregation, activation of the coagulation system, and endothelial cell dysfunction.Objective:To investigate the serum level of anti angiogenic factor soluble fms-like tyrosine kinase-1 (sFlt-1) in the third trimester of preeclamptic pregnants in relation to the Doppler ultrasonography indices.Methods:One hundred and five pregnant women at the Pediatric and Maternity Teaching Hospital in Hilla City were studied. All of them were in their third trimester and with singleton pregnancy. All participants were reexamined one month following delivery.Results:The body mass index, spot urine protein to creatinine ratios and mean pulsatility index, resistance index), systolic and diastolic blood pressures were increased in preeclamptic groups. Post-delivery systolic and diastolic blood pressures increased in the control pregnant group and significant reduction in the both preeclamptic groups compared with the systolic and diastolic blood pressures at third trimester of pregnancy. sFlt-1 levels were increased in severe than mild preeclampsia and control groups. In post-delivery period, the sflt-1 decreases in the control pregnant, mild and severe preeclamptic groups in comparison to the third trimester. In preeclampsia, the sflt-1 is positively correlated with blood pressure, protein: creatinine ratio, body mass index, resistance index, pulstality index, total serum protein, and negatively correlated with neonatal weight and gestational age at delivery.Conclusion:The changes in anti angiogenic factors sFlt-1 during pregnancy and in post-delivery period stress its role in the pathogenesis of preeclampsia and could be used to predict the disease progression and impact on the outcome of pregnancy.Keywords: Preeclampsia, sFlt-1, Doppler indices.
Keywords: Preeclampsia; sFlt1; Doppler indices